A novel source of phytochemical and bioactive peptide from fermented mushroom trimming waste extract by Bifidobacterium longum - Napassorn Peasura; Pornrat Sinchaipanit; Kanokwan Yodin (Applied Food Research)
The extract from agricultural waste, (golden needle mushroom trimmings) was extracted and fermented with B. longum at 37 °C for 0, 24, 48, and 72 h. The chemical changes and phytochemicals were investigated, as well as antioxidant activity during fermentation, and biological activities such as angiotensin-converting enzyme (ACE) inhibition were investigated. The results found that the growth of B. longum was increased during 0–24 h, while viability declined after 24 h. The greatest concentrations of phenolic compounds and flavonoids were observed at 709.81 and 42.07 mg/mL, respectively. The antioxidant activity levels measured using the 2,2-diphenyl-1-picrylhydrazyl (DPPH•) and 2,2′ -azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS•+) assays were 42.65 % and 45.24 %, respectively. The biological activity, particularly ACE inhibition, was assessed in vitro and was correlated with blood pressure regulation. The fermented mushroom trimming extract had a maximum ACE inhibition value of 9.91 % and a half-maximal inhibitory concentration (IC50) value of 2,134.08 mg/L, making it more effective than the control group with an IC50 value of 2,482.36 mg/L.